(untitled) (Philological Studies, 2019)
Macedonian Literature is the youngest among all the Slavic Literatures at the same time it has its ancient roots. After 1945 whwn Macedonians had its ancient roots. After 1945 when Macedonians had established their own State as a part of Federal Republic of Yugoslavia, Macedonian Literature finally had an opportunity for intensive growth and Macedonian language had standardized its norms. During the same period Modern system of genres in Macedonian Literature has been created. The literary classics has appeared soon after and Macedonian literary tradition has been enriched by several new names – Blazhe Koneski, Zhivko Chingo, Aco Shopov, Petre M. Andreevski. Macedonian Literature has been based on local folklore and has assimilated the experience of world and Slavic Literatures.